The Contribution of Self-Compassion to Influencing Adolescent Resilience - Abi Fa’izzarahman Prabawa; Nova Setyawan; Eni Rindi Antika; Galuh Nadhita; Alvia Ainil Lathifah (Proceedings Series of Educational Studies, 2023)
The rising cases of suicide indicate the fragile mental state of teenagers (Strawberry Generation) when dealing with problems. This suggests that teenagers are not resilient enough, meaning their ability to adapt and withstand difficult situations is still low. This condition is influenced, in part, by a lack of warmth, understanding, and the ability to help oneself (self-compassion). This research aims to examine the influence of self-compassion on teenage resilience. The research approach used is quantitative with an ex-post facto design. The study involved 1512 teenagers (aged 11-18) in Central Java, selected using convenient random sampling. The research instruments used were a resilience scale (24 statement items, referring to Ungar's theory in 2013) and a self-compassion scale (26 statement items, based on Neff's theory in 2003). The instruments underwent validity testing (validity values exceeding the table's R) and reliability testing (self-compassion scale 0.781 and resilience scale 0.786). Data were analyzed using simple regression tests and met classical assumption tests. The research results show that self-compassion has a positive effect on resilience with an R Square value of 0.348, meaning that self-compassion contributes 34.8% to resilience. This research has implications for guidance counselors to provide services to enhance teenagers' self-compassion, thus improving their resilience.